2022
DOI: 10.1177/25158414221132825
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal thickness in patients with systemic arterial hypertension: a systematic review and meta-analysis

Abstract: Background: The global burden of hypertension is constantly increasing with adverse cardiovascular and ocular sequelae. The association between elevated blood pressure and choroidal thickness (CT), as assessed via optical coherence tomography (OCT), is poorly understood. Objectives and Design: Studies including hypertensive adults and normotensive controls undergoing OCT were evaluated for inclusion in this meta-analysis. The primary endpoint was CT difference between hypertensive and normotensive adults. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Both OCT and OCTA have already proven their use in evaluating patients with cardiovascular diseases. The impact of arterial hypertension on choroidal thickness and retinal microvascularization has been investigated by OCT [8] and OCTA [9], validating the fact that hypertensive patients show reduced choroidal thickness and lower superficial and deep vascular density compared to healthy controls. In patients with chronic heart failure and reduced left ventricular ejection fraction (LVEF), Alnawaiseh et al [10] identified reduced retinal and optic nerve head perfusion through OCTA.…”
Section: Introductionmentioning
confidence: 73%
“…Both OCT and OCTA have already proven their use in evaluating patients with cardiovascular diseases. The impact of arterial hypertension on choroidal thickness and retinal microvascularization has been investigated by OCT [8] and OCTA [9], validating the fact that hypertensive patients show reduced choroidal thickness and lower superficial and deep vascular density compared to healthy controls. In patients with chronic heart failure and reduced left ventricular ejection fraction (LVEF), Alnawaiseh et al [10] identified reduced retinal and optic nerve head perfusion through OCTA.…”
Section: Introductionmentioning
confidence: 73%
“…In this study, healthy subjects evaluated at the Eye Unit, Department of Medicine, Surgery and Dentistry, "Scuola Medica Salernitana", University of Salerno, Salerno, Italy, were recruited for the period from January 2020 to November 2021. Subjects with systemic and ocular pathologies that could have influenced the measurements, such as diabetes, hypertension, smoking, carotid artery stenosis, Parkinson's disease, Alzheimer's disease or cognitive impairment and ocular conditions such as pseudoexfoliation syndrome and amblyopia were excluded from this study [15][16][17][18][19][20][21][22][23]; additionally, patients who had undergone ocular surgery, patients under 18 or over 70 and pregnant patients were not included in this work. All the participants were thoroughly informed about the purpose of this study, and written informed consent was obtained from each of them.…”
Section: Patient Selectionmentioning
confidence: 99%
“…No single theory can perfectly resolve the complex and conflicting results of different studies. Additionally, other systemic and ophthalmic conditions can also exert influence on choroidal parameters, such as hypertension [ 13 ], hyperlipidemia, amblyopia [ 14 ], or myopia. Therefore, CTh in patients with diabetes may be influenced by factors that have not been previously identified, leading to conflicting results across studies.…”
Section: Introductionmentioning
confidence: 99%